Son of Son of Sam: Trashing Popular Media and Criminalizing Crime-Related Expression - Sternbach, David (1997)
When the Supreme Court struck down New York's Son of Sam statute on First Amendment grounds, it nonetheless found that states have an undisputed compelling interest in ensuring that criminals do not profit from their crimes. The Court in effect invited states and lower courts to find less restrictive means to restrict crime-related expression, yet declined to address the question of how, or whether, expression-related income can be considered profit from crime. This Article examines that question, and discusses judicially-imposed restrictions on receipt of payment for expression deemed to be crime-related, including fines intended to forestall sales of stories by indigent criminals and sentencing decisions influenced by defendants' television appearances. In particular, the Article considers the case of former radical activist Katherine Anne Power, who unsuccessfully challenged a probation condition forbidding her from directly or indirectly engaging in benefit generating activity relating to the publication of facts pertaining to her thoughts, feelings, opinions or emotions about her crime or her twenty-three years underground. The author sets the Power case in the context of First Amendment doctrine as it concerns content-based financial disincentives to speech, as well as numerous lower-court opinions in which judges openly express hostility to crime-related expression and the popular media that publish and report such expression. This Article demonstrates that judicial attitudes have improperly influenced the choice and application of legal standards in these cases, resulting in a subset of disfavored speech not otherwise recognized in First Amendment jurisprudence. The author concludes that ample alternatives exist for punishing crime and compensating victims without burdening speech, and that judges have significantly overreached by considering both the content of, and venues for, expressive activity